A Cultural History of Tarot : From Entertainment to Esotericism | WorldCat.org
"The enigmatic and richly illustrative tarot deck reveals a host of strange and iconic images, such as The Tower, The Wheel of Fortune, The Hanged Man and The Fool: over which loom the terrifying figu